Autoassociação de amidas aromáticas: abordagem supramolecular e mecanismos de cristalização - Pagliari, Anderson Berti (2017)
This work presents the use of N-phenylamides as models for the study of self-association and intermolecular interactions. Obtaining the crystal of N-phenyltrifluoroacetamide allowed its diffraction and inclusion in the series to be studied. The N-phenylamides with H, CH3, (CH3)3, Ph, CF3, CCl3 and CBr3 substituents were used together with the supramolecular cluster approach to obtain topological and energetic data and to verify differences in crystalline packing. Analyzes were carried out through several tools including theoretical calculations at the ωB97X-D/cc-pVDZ level, molecular electrostatic potential (MEP), quantum theory of atoms in molecules (QTAIM) and NMR. After the use of the tools, it was observed that the more energetic dimers were governed mainly by the hydrogen bond NH···O. Through the energy data, it was possible to propose crystallization mechanisms. Growth through chains in the early stages has been observed for almost all compounds, mainly due to the NH···O interaction, which helps to anchor molecules. Significant differences were observed between proposed mechanisms. For the solution study, 1H NMR spectroscopy was used in order to obtain the variation of the chemical displacements as a function of the concentration. By monitoring the amide hydrogen, it was possible to obtain the association constants of the molecules (Ka). The correlation of Ka data with the hydrogen bond strength (GNH···O) showed a good trend, showing a direct relationship between experimental and theoretical data.